(untitled) (UNED Research Journal, 2025)
Introduction: In Central America, forestry exploitation and agricultural expansion have raised concerns about biodiversity conservation, including bird diversity. Objective: To assess host-parasite relationships and habitat influence in birds and their ticks across forest fragments with varying degrees of alteration. Methods: From February 2008 to June 2010, we sampled nine forest fragments, classified by logging and agricultural use, at the Huetar Norte Conservation Area, Costa Rica. With mist nets we captured 838 birds and collected feces, blood, oropharyngeal and cloacal swabs, along with 555 ectoparasites from 407 birds. We analyzed samples using flotation technique, Hoyer, DNA and RNA extraction, and PCR. Results: The frequencies of endoparasites did not differ by level of forest alteration or agricultural use; only six Amblyomma spp. ticks were positive for Rickettsia spp. These were found in the non-harvested/low crop intensity, non-harvested/high crop intensity, and harvested/high crop intensity categories. No Anaplasma spp., Borrelia spp. or Chlamydia psittaci were found. Conclusion: These sites were similar regarding bird health status and pathogens. These results seem to support the dilution effect proposed for habitat fragmentation and transmission of infectious agents.